Implementation of EDFAT Technique in the Creation of Photo Story about Galeri Foto Jurnalistik Antara - Alyatalatthaf, Muhammad Dicka Ma'arief; Kusumawati, Dyah (Institut Seni Indonesia Yogyakarta, 2023)
Photo story is a genre in photography which aims to capture various life events with a chronological plot that has a narrative aspect. It is enable us to tell a story in several photo that represent reality holistically. A photography technique known as EDFAT is also used to aid in the creation of works. The goal of this research is to use the EDFAT technique to create photo story works at Galeri Foto Jurnalistik Antara. The results of this study,